Genetic Diversity Approach to Fishery Management Spiny Lobster Southern Waters of Java Based on SWOT Analysis and AHP - Florensius Eko Haryono; Ambariyanto Ambariyanto (Journal Omni-Akuatika, 2017)
Indonesia as an archipelagic and tropical country, and known as the centre of megabiodiversity. Tropical spiny lobster consists of several species and able to survive without water for a certain period and this excess used to be distributed life conditions.  Spiny lobster fisheries is become an important issue in Indonesia now, due to the catch condition decrease for some decade, and need a policy to manage. Spiny lobster management strategy based on biodiversity genetic of lobster in Southern of Central Java (SCJ) and Special  Region of Jogjakarta (SRJ) waters done by collecting the lobster randomly, and collecting the questioner to fisherman, lobster collector, government and NGO from February-August 2015.  Data analyzed by SWOT and AHP methods.   The management priorities based on highest score. The first priority management based on genetic of lobster is not carried out on an isolated by each districts. Second priority management based on genetic lobster was avoid of each district management. Third priority was  optimizing new fishingground.  Fourth priority optimized of habitat utilization, optimized  fishing time, and increased number of fishing trips .Key word : Spiny lobster, diversity genetic, SWOT, AHP.